A Prospective Study on Evaluation of Antibiotic Usage Pattern in Hospitals - Patel, Rutul; Patel, Rohan; Patel, Komal; Soni, Meshwa; Rathod, Priyanshee; Deshpande, Shrikalp (Indian Journal of Pharmacy Practice)
Background: Antibacterials are the most imperative weapons in our hands accounting for majority of ambulatory care prescriptions and one of the most irrationally prescribed drugs. Irrational usage can lead to treatment failure, increase cost burden, lack of availability of drug molecule to treat life-threatening infections and affect patient’s quality of life significantly. Aim: To study the usage pattern of antibiotics in hospitals. Objectives: The primary objective was to assess the prescribing pattern of antibiotics. The secondary objectives of study were to study World Health Organization prescribing indicators for antibiotics, calculate the Defined Daily Dose and to evaluate the cost burden. Materials and Methods: A prospective study was conducted for 6 months with 405 patients. Self-designed proforma for data collection was used. Anatomical Therapeutic Chemical Classification System classification and Defined Daily Dose system was used for the quantification of drug utilization. Descriptive statistical analysis was done using Microsoft excel and Statistical Package for Social Sciences. Results: Average hospital stay was 5.27±1.93 days. Out of 4934 prescribed drugs, 860 were antibiotics of which 641 were in parenteral formulation. Most of the antibiotics were prescribed by brand name. Cephalosporin/B-lactamase inhibitor (22.97%) was the largely prescribed class. Antibiotics shared 50.04% of the total cost of all drugs. Culture test was performed in 34 patients. Conclusion: Performing the culture sensitivity test before prescribing antibiotics should be implemented which can reduce the expense, client frustration with blind antibiotic trials, lower the risk of complications and antibiotic resistance, and improve the chance and speed of patient’s recovery.
Keywords: Antibiotics; cost; DDD; Resistance; Usage pattern